1997
DOI: 10.1093/fampra/14.3.194
|View full text |Cite
|
Sign up to set email alerts
|

'Ending up a GP': a qualitative study of junior doctors' perceptions of general practice as a career

Abstract: Junior doctors' perceptions of general practice are expressions of a hospital-centric culture. Criteria for career choice are diffuse and complex. There was no evidence that the 1990 GP Contract deterred recruitment. The compromise between intrinsic satisfaction and lifestyle may be significant for GP morale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 0 publications
3
44
1
Order By: Relevance
“…The importance of lifestyle factors has been highlighted previously 2,13,15 but not as the main motivator for this career choice. A 1995 survey of GP registrars found that 91% considered having time for leisure activities to be an important factor when choosing a future career, and that 72% would have been glad to remove the requirement for 24-hour patient cover.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
See 3 more Smart Citations
“…The importance of lifestyle factors has been highlighted previously 2,13,15 but not as the main motivator for this career choice. A 1995 survey of GP registrars found that 91% considered having time for leisure activities to be an important factor when choosing a future career, and that 72% would have been glad to remove the requirement for 24-hour patient cover.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…2,13,14 Interviews with junior doctors in 1997 revealed a perception that general practice had inferior clinical content but a superior lifestyle to hospital medicine; as such, choosing general practice as a career was often based on negative judgements. 2 This finding differs from the current results, which show that negative reasons for choosing general practice are relevant to only a minority of current trainees and newly qualified GPs.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…3,4 This must be replaced by respect and understanding throughout medicine that all specialties are important, that all specialties have their own set of skills and values, and that the NHS will only function properly when we have sufficient numbers of doctors practising all specialties.…”
mentioning
confidence: 99%